Wawacan as a Medium for Da'wah: Islam and Sundanese Culture in the Story of Perbu Kean Santang - Ramadhian Fadillah; Dedi Supriyadi (Universitas Pakuan, 2025)
This study examines Wawacan Perbu Kean Santang as a traditional Sundanese literary text that represents Islamic preaching through a cultural approach. The character Kean Santang in the wawacan is positioned as a symbolic figure who reflects the process of acculturation between Islamic teachings and Sundanese culture in the context of Islamization in West Java. This study aims to analyze the form, content, and strategies of Islamic preaching conveyed through the narrative and symbolic structure of the text. The method used is descriptive qualitative with a philological and cultural literary approach. The data consists of text excerpts containing Islamic preaching values, such as tauhid, akhlak, worship, and moral values. The results show that Islamic preaching in Wawacan Perbu Kean Santang is conveyed through symbolic narratives and heroic figures that are in harmony with the Sundanese way of life, thus enabling the peaceful acceptance of Islam without negating local traditions. This study confirms that wawacan functions not only as a literary work but also as a medium for preaching and a means of cultural acculturation in the process of locally based Islamization. Keywords: cultural acculturation, Islamic preaching, Kean Santang, Sundanese literature, wawacan